CONFLICT OF MEANINGS IN CIAMSI PREDICTION TEXTS (HERMENEUTICS OF CIAMSI PREDICTION TEXTS AT VIHARA DHARMA BHAKTI AND DHARMA JAYA TOASEBIO) - Daniel Susanto; Fabianus Fensi (Pelopor Publikasi Akademika, 2023)
Ciamsi, a long-standing historical legacy, continues to be popular to this day, serving as concrete evidence of its enduring appeal. Spanning the tumultuous shifts of historical epochs, Ciamsi has persevered and been preserved within various temples, both large and small, playing a pivotal role as a divination tool. The enduring presence of Ciamsi not only underscores its unquestionable intrinsic value but also reflects the unwavering spirit of Chinese tradition and its cultural heritage. Consequently, this research is deeply rooted in the environment of centuries-old temples in Jakarta, where Ciamsi has become an inseparable part of the local cultural fabric. The primary objective of this research is to delve profoundly into the intricate meanings and interpretations embedded within Ciamsi. Additionally, the research aims to unveil the profound role of symbolism within the realm of Ciamsi, as employed by Vihara Dharma Bhakti and Vihara Dharma Jaya Toasebio. To achieve these objectives, this study employs the comprehensive hermeneutical framework introduced by the eminent philosopher, Paul Ricouer. This research fundamentally aligns with the qualitative research paradigm, enabling a profound and nuanced understanding of the subject matter.